Morphological Assessment of the Effect of Nanosecond Diode Laser Radiation With a Wavelength of 1265 nm on Periodontal Tissue in the Treatment of Apical Periodontitis: An Experimental Study: The Effect of Laser Radiation on Periodontal Tissue in the Experiment - Chunikhin, Nikita A.; Bazikyan, Ernest A.; Chunikhin, Andrey A.; Klinovskaya, Anna (Journal of Lasers in Medical Sciences, 2021)
Introduction: There is a morphological assessment of the damaged area and the inflammatory response of periodontal tissues after therapy. It seems relevant to evaluate the reaction of the periapical tissues of the teeth of experimental animals after the treatment of simulated apical periodontitis using laser photodynamic therapy (PDT) and non-pigment laser transcanal microablation using morphological research. Methods: The lower incisors of 15 rabbits were used to simulate acute apical periodontitis of pulpal origin. Subsequently, the traditional treatment of teeth canals using mechanical cleaning and irrigation with antiseptic solution started. Then, three groups underwent different therapies - using PDT (n = 5; photosensitizer chlorin e6, [l = 660 nm, 60 mW/cm2 ] for 2 minutes), using a new technology of transcanal laser ablation (n = 5; diode laser [l = 1265 nm, 180 mW/cm2] for 3 minutes), and without additional treatment (n = 5). Laser therapy in two groups was carried out for 10 days once in 2 days. The animals were euthanized 10 days after the treatment started, decapitation was performed, and morphological specimens were studied under a microscope. Descriptive analysis (study of inflammatory apical infiltrate, bone regeneration of the alveoli and periodontal ligament) and quantitative analysis were performed. The data were statistically processed using the KruskalWallis test. Results: The group treated with the new laser technology showed the best results with moderate lymph-macrophage infiltration and congested vessels, moderate neoangiogenesis, and fibrogenesis. The size of the lesion was 506.4 mm2, compared with the PDT group - 872.0 mm2 (P≤0.05). Conclusion: A decrease in the focus of inflammation, moderate neoangiogenesis, and fibrogenesis in the periapical region when using transcanal laser microablation indicates the prospects of using the new technology in clinical practice in the complex therapy of apical periodontitis. DOI:10.34172/jlms.2021.43